2020
DOI: 10.1111/cts.12742
|View full text |Cite
|
Sign up to set email alerts
|

Role of Elevated SFLT‐1 on the Regulation of Placental Transporters in Women With Pre‐Eclampsia

Abstract: Pre-eclampsia (PE) is an obstetric complication associated with elevated levels of fms-like tyrosine kinase 1 (sFlt-1) and dysregulated trophoblast differentiation. However, limited information exists on the expression and regulation of placental drug transporters in PE. Transporter mRNA and protein expression were analyzed in human placentas diagnosed with PE (n = 34) and gestational age-matched controls (n = 24), whereas placental BeWo cells were treated with angiogenic factors in vitro. Significant downregu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
21
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(24 citation statements)
references
References 43 publications
2
21
1
Order By: Relevance
“…In our study, OATP2B1 expression remained unaffected following CSE treatment, whereas in the placental explants OATP2B1 decreased in a time-dependant manner following CSE treatment. This finding is contrary to previous findings (Kojovic et al, 2020), where OATP2B1 expression was increased in preeclamptic placentae (Kojovic et al, 2020). This could be due to differences between explant phenotypes used, as Kojovic et al, utilized placental tissues obtained from preeclamptic women and here cesarian-derived placental explants were stimulated with CSE.…”
Section: Discussioncontrasting
confidence: 74%
See 1 more Smart Citation
“…In our study, OATP2B1 expression remained unaffected following CSE treatment, whereas in the placental explants OATP2B1 decreased in a time-dependant manner following CSE treatment. This finding is contrary to previous findings (Kojovic et al, 2020), where OATP2B1 expression was increased in preeclamptic placentae (Kojovic et al, 2020). This could be due to differences between explant phenotypes used, as Kojovic et al, utilized placental tissues obtained from preeclamptic women and here cesarian-derived placental explants were stimulated with CSE.…”
Section: Discussioncontrasting
confidence: 74%
“…Interestingly, oxidative stress and inflammation can also affect OATP2B1 expression (Kojovic et al, 2020). For example, a study by Kojovic et al, reported that OATP2B1 expression was increased in placentae obtained from women with preeclampsia (a pregnancy-specific disorder often characterized by increased oxidative stress and increased proinflammatory cytokines) (Kojovic et al, 2020). An alteration in the expression of functionally essential transporters (such as OATP2B1) suggests that placental function is compromised during pregnancy complications.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, exposure of human BeWo trophoblast cells to sFlt-1 reduces BCRP expression by 85 to 90% which can be rescued by vascular endothelial growth factor. These findings may be important in understanding transporter regulation during pre-eclampsia (Kojovic et al, 2020b). Epigenetic factors may also play a role in transporter regulation during disease.…”
Section: Pathways Regulating Abc Transporter Expression During Pregnancy Complicationsmentioning
confidence: 84%
“…In general, placentas from pre-eclamptic pregnancies tend to exhibit reduced transporter expression when evaluated by microarray (Herse et al, 2007;Nishizawa et al, 2007;Founds et al, 2009;Pantham et al, 2012;Vaiman et al, 2013;Gormley et al, 2017). Additional studies where mRNA and protein expression were quantified confirm that pre-eclampsia is often associated with reduced expression of placental MDR1, MRP1, 2, and BCRP transporters though some transporters are unchanged or slightly increased (Afrouzian et al, 2018;Kojovic et al, 2020b). When pre-eclampsia is severe and early in its onset, a prominent reduction in placental MDR1 protein expression has been observed (Dunk et al, 2018).…”
Section: Abc Transporter Alterations Human Placenta Explants and Biospecimens From Patients Diagnosed Withmentioning
confidence: 88%
“…The mRNA expression of BCRP, OAT4, OATP2B1, and OCT3 was determined in the treated and untreated (control) explants, using qRT-PCR, as previously described [21]. In brief, RNA was extracted from placental explants using Trizol (Invitrogen, Carlsbad, CA, USA) and total RNA concentrations were quantified using the NanoDrop 1000 spectrometer (Thermo Fisher Scientific.…”
Section: Quantitative Real-time Pcr Analysismentioning
confidence: 99%